Internet Addiction among Senior Secondary School Students in Relation to Socio Economic Status and Perceived Loneliness (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to explore the Internet Addiction among Senior Secondary School Students in Relation to Socio Economic Status and Perceived Loneliness. This study comprised a sample of 736 senior secondary students of Amritsar, Punjab. Data was gathered by internet addiction scale developed by investigator, socio economic scale and perceived loneliness scale. Variance test shows that normal lonely students are more inclined to internet addiction than non lonely students. Moreover, the highly lonely students are more addicted to internet than non lonely students. In addition to this, highly lonely are prone to internet addiction than normal lonely students. So, we can say that highly lonely students are most addicted to internet followed by normal lonely students; however non lonely students are least internet addicted.